2017
DOI: 10.1007/s12288-017-0910-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cell Dyscrasias in India-2017 Updates

Abstract: Rapid advances are being made in the field of plasma cell dyscrasias. Many abstracts pertaining to the laboratory aspects, clinical features, treatment modalities and outcome of plasma cell dyscrasias were presented at Hematocon 2017. All the total of 24 abstracts pertaining to plasma cell dyscrasias presented at the Hematocon 2017 were reviewed. Out of them 10 were original research and 14 were case reports/short case series. The key findings of original research studies conducted in India are being summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In light of this it is also important to understand that such mHealth application for RMNCH would thus be more useful in weaker states where the reasons for poor coverage are linked more with the demand for service. For example, the Coverage Evaluation Survey reported that poorer states such as Bihar and Uttar Pradesh have low rates of RMNCH service utilization, a large portion of which is explained by lack of awareness and knowledge about the importance of services [ 36 ]. The findings from our impact assessment study suggested an increase in knowledge and thereby utilization of MNCH services after introduction of ReMiND program [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of this it is also important to understand that such mHealth application for RMNCH would thus be more useful in weaker states where the reasons for poor coverage are linked more with the demand for service. For example, the Coverage Evaluation Survey reported that poorer states such as Bihar and Uttar Pradesh have low rates of RMNCH service utilization, a large portion of which is explained by lack of awareness and knowledge about the importance of services [ 36 ]. The findings from our impact assessment study suggested an increase in knowledge and thereby utilization of MNCH services after introduction of ReMiND program [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvements in the varied aspects of the myeloma management, the major challenge we face is the heterogeneity of care provided by the physicians in India [8,9]. We require nation specific consensus guidelines which take into consideration the local issues, heterogeneity of the resources and biology of the Indian patients.…”
mentioning
confidence: 99%